A systematic review on the association between the Helicobacter pylori vacA i genotype and gastric disease. Issue 5 (5th April 2016) - Liu, Xian; He, Bangshun; Cho, William C.; Pan, Yuqin; Chen, Jie; Ying, Houqun; Wang, Feng; Lin, Kang; Peng, Hongxin; Wang, Shukui
Abstract : Helicobacter pylori ( H. pylori ) has been recognized as a cause of gastrointestinal diseases and progress of the pathology of gastrointestinal diseases is related to the genotype of H. pylori . Published studies have indicated that the H. pylori vacuolating cytotoxin gene A ( vacA ) i1/i2 genotype is associated with peptic ulcer disease (PUD) and gastric cancer (GC), but their conclusions are inconsistent. This study aimed to further assess the risk of vacA i gene for PUD and/or GC. A systematic search was conducted across three main electronic databases (PubMed, Web of Science, and CNKI). A meta‐analysis was then performed on the pooled data of the published articles to estimate the overall influence of vacA i polymorphisms on PUD and/or GC by crude odds ratio (OR) with 95% confidence intervals (CI). The reliability of the results were confirmed by publication bias and sensitivity analysis of included studies. A total of 14 studies were selected according to the specific inclusion and exclusion criteria. The pooled results revealed that patients with GC were more vulnerable to infection by H. pylori i1 genotype (OR = 5.12; 95% CI: 2.66–9.85; P < 0.001) than those with chronic gastritis or nonulcer disease. Moreover, the results of subgroup analysis indicated that the i1 genotype of H. pylori was associated with an increased GC risk (OR = 10.89; 95% CI: 4.11–20.88; P < 0.001) in the Middle Asian population. The H. pylori vacA i1 genotype is associated with an increased GC risk, especially in the Middle Asian population.